Changes in Knowledge, Behavior and Environmental Control for Filariasis Prevention with Ã¢â‚¬Å“MANDIRIÃ¢â‚¬Â Pocket Book on Society in Pekalongan City: A Longitudinal Study - Siwiendrayanti, A.; Pawenang, E. T.; Indarjo, S.; Wulandhari, S. A. (Jurnal Pendidikan IPA Indonesia, 2019)
Mass Drug Administration (MDA) coverage for filariasis in Indonesia increased from 37.7% in 2011 to 73.9% in 2014. In contrast, filariasis case increased from 11,902 in 2012 to 14,932 in 2014. Pekalongan City has the highest number of filariasis cases in Central Java, Indonesia. The city has been implementing MDA but it has not decreased the filariasis case numbers. Pekalongan City societyÃ¢â‚¬â„¢s knowledge and participation in filariasis elimination efforts were still in the low level. Reading can increase knowledge and influence behavior. Changing certain behaviors is a complex matter that takes a long time. This study is aimed to assess the changes in knowledge, behavior, and environmental control in the filariasis prevention by implementing Ã¢â‚¬Å“MANDIRIÃ¢â‚¬Â Pocket Book for three years (from 2015 to 2017). This research is a quasi-experiment one with randomized control group pretest-posttest design, done in 2 villages of Pekalongan City. Ã¢â‚¬Å“MANDIRIÃ¢â‚¬Â Pocket Book Program was able to achieve proper results in 6 months (April-September 2016). This study proves that the proper results were persistent in the following 9 months (July 2017). Compared to that of the control group, the result of the experiment group shows an improvement in knowledge, repellent application behavior, night outdoor behavior, and indoor environmental control.